Stomach ailments and digestive disturbances - Murray, Michael T. (Getting well naturally series, 1997)
Chronic stomach ailments send millions of Americans to the pharmacy for over-the-counter remedies. Conditions ranging from esophageal reflux to colitis, ulcers, and gas make life miserable for many. In this book, Dr. Murray brings his Getting Well Naturally approach to readers looking for relief and life beyond Maalox.